Abnormal glymphatic system in patients with autoimmune encephalitis: Relationship with cognitive performance - Yingchi Zhang; Dianwei Wu; Zhirong Fan; Xiuxiu Leng; Ting Wan; Xiaodan Shi; Xiaomu Wang; Xuan Wang; Changgeng Song; Fang Du; Wen Jiang (Brain Research Bulletin)
Objectives: We aimed to explore the impact of glymphatic function in patients diagnosed with autoimmune encephalitis (AE). Methods: In this prospective longitudinal study, patients were recruited from Xijing Hospital between June 2020 and January 2024. Glymphatic function was evaluated using diffusion tensor imaging analysis along the perivascular space (DTI-ALPS). Cognitive impairment was defined as a Montreal Cognitive Assessment (MoCA) score below 26 at the 12-month follow-up. Results: A total of 115 individuals were enrolled, including 85 patients with AE and 30 age- and sex-matched healthy controls (HCs). After correcting for age and sex, patients with AE had a significantly lower baseline ALPS index compared to HCs (1.173, 95 % CI [1.135, 1.210] vs. 1.456, 95 % CI [1.371, 1.541]; P < 0.001). The baseline ALPS index was correlated with cognitive performance, including a positive correlation with the Mini-Mental State Examination (MMSE) score (r = 0.568, P < 0.001) and a positive correlation with the MoCA score (r = 0.645, P < 0.001). In the longitudinal study, the ALPS index gradually increased over the follow-up period (P < 0.001), and a low level of the baseline ALPS index was associated with a higher risk of long-term cognitive impairment (HR [95 % CI] = 1.70 [1.12–2.58], P = 0.013). Conclusion: The glymphatic system is impaired in AE patients. A decreased DTI-ALPS index is associated with a decline in cognitive performance. Additionally, a low baseline ALPS index may predict an increased risk of long-term cognitive impairment in AE patients.